Protective Effect of Arctigenin against MPP+ and MPTP-induced Neurotoxicity - Li, Dongwei; Liu, Qingping; Jia, Dong; Dou, Deqiang; Wang, Xiaofei; Kang, Tingguo (Planta Medica, 2014)
The potential protective effects of arctigenin on 1-methyl-4-phenylpyridinium ion and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyride-induced neurotoxicity were examined, and the results indicated that arctigenin could improve the movement behaviors and upregulate dopamine and γ-aminobutyric acid levels in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyride-induced neurotoxicity mouse model. A further in vitro experiment showed that the pretreatment with arctigenin on cultured human neuroblastoma SH-SY5Y cells could obviously attenuate the decrease of cell survival rates caused by treatment with 1-methyl-4-phenylpyridinium ion by way of acting against cell apoptosis through the decrease of Bax/Bcl-2 and caspase-3, and by antioxidative action through reduction of the surplus reactive oxygen species production and downregulation of mitochondrial membrane potential. It is for the first time that a neuroprotective activity of arctigenin in both in vitro and in vivo experiments was reported, enlightening that arctigenin could be useful as a potential therapeutic agent for Parkinsonʼs disease.
Keywords: arctigenin; oxidative stress; anti-apoptosis; neuroprotective effect; Parkinsonʼs disease